Revision of the New World species of Erythrodolius (Hymenoptera: Ichneumonidae: Sisyrostolinae), with a key to the world species - Bennett, Andrew M.r.; Sääksjärvi, Ilari E.; Broad, Gavin R. (Zootaxa, 2013)
The genus Erythrodolius previously comprised ten species of ichneumonids: nine from Madagascar and one from Costa Rica. The current study revises the New World species of Erythrodolius including descriptions of three new species from Central America which brings the world total to 13 species: E. incompletus sp. n., E. luteus sp. n. and E. tenebrosus sp. n. A key to the world species is provided. Justification for the preference of the subfamily name Sisyrostolinae instead of Brachyscleromatinae is provided.